Ações de prevenção relacionadas a violência ocupacional dos trabalhadores da área da saúde da rede de atenção à saúde de Campo Grande/MS - Rodrigues, Josyenne Assis (2021)
Preventing violence against healthcare workers is a complex issue due to the variation in the purpose and design of healthcare facilities and the diverse functions performed by the numerous direct and indirect care occupations encompassed in the healthcare sector. The main objective of this study was to understand the prevention actions related to violence in the workplace of workers in the health area of the Health Care Network of Campo Grande/MS. Materials and methods: Quantitative and qualitative study, exploratory, analytical, cross-sectional, conducted in five Health Districts in the city of Campo Grande/MS, Brazil, from October to December 2020. Workers participated in the study. from different areas, namely: doctors, nurses, nursing assistants and/or technicians, dentists, speech therapists, social workers, pharmacists, community health agents, administrative staff and psychologists. The quantitative phase took place through a sociodemographic and professional questionnaire and the use of a semi-structured questionnaire on the assessment of violence at work. The qualitative phase was through semi-structured interviews. The analysis of quantitative data was performed using a tabular representation, consisting of absolute and relative frequency, with the respective 95% confidence interval. To verify possible associations between the study variables, the Chi-square test, Chi-square trend test, Fisher's exact test and Cox regression were used. The statistical programs Epi-info™ 7.2.4 and Bio Estat 5.3 were used. The analysis of qualitative data followed the precepts of Thematic Analysis, for the construction and generation of data coding in a systematic way, we used the Atlas.ti9 software version 9, we chose to build thematic maps. The research was approved by the Research Ethics Committee of the Federal University of Mato Grosso do Sul on May 21, 2020 under opinion No. 4.041.407 and CAAE: 28384619.2.0000.0021. The results showed that in relation to violence in the workplace, 76,4% of professionals reported that they had already suffered, of these (n=133), 95,5% suffered from verbal violence, 36,9% moral or psychological violence, 19,6% physical violence and 12,8% violence due to sexual harassment. There was an approximately 6 times higher prevalence of sexual harassment among females. Regarding physical violence, the majority (96, 2%; n=26) occurred with the use of a weapon (object, knife or revolver), the authors of the incidents were mainly patients (73, 1%) and their families (34, 7%). Prevention actions focused on measures to reduce violence (28, 8%) for professionals (n=174) related to workers' health, educational component, behavioral component, professional valuation and awareness about violence at work. From the perspective of health workers, violence prevention is directly related to the applicability of the National Humanization Policy in health services and the implementation of notification of violence in the workplace. The conclusion of this study is that prevention of violence against health workers in the workplace involves environmental safety, workers' health, training to prevent violence and the articulation of Health Care Networks.